2011
DOI: 10.1074/jbc.m110.176461
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Serglycin Proteoglycan in Mast Cell Apoptosis Induced by a Secretory Granule-mediated Pathway

Abstract: Mast cell secretory granules (secretory lysosomes) contain large amounts of fully active proteases bound to serglycin proteoglycan. Damage to the granule membrane will thus lead to the release of serglycin and serglycin-bound proteases into the cytosol, which potentially could lead to proteolytic activation of cytosolic pro-apoptotic compounds. We therefore hypothesized that mast cells are susceptible to apoptosis induced by permeabilization of the granule membrane and that this process is serglycin-dependent.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
45
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 57 publications
9
45
0
Order By: Relevance
“…Unexpectedly, we noted signs of the presence of active caspase-3 even in the absence of cell deathinducing agent (13). Possibly, the activated caspase-3 could have been present in an apoptotic subpopulation of the primary mast cell population used for those studies.…”
Section: Resultsmentioning
confidence: 84%
See 3 more Smart Citations
“…Unexpectedly, we noted signs of the presence of active caspase-3 even in the absence of cell deathinducing agent (13). Possibly, the activated caspase-3 could have been present in an apoptotic subpopulation of the primary mast cell population used for those studies.…”
Section: Resultsmentioning
confidence: 84%
“…In a previous study, we showed that mast cells are sensitive to cell death induced by secretory granule-permeabilizing agents, and that mast cell apoptosis in response to such agents is accompanied by caspase-3 activation (13). Unexpectedly, we noted signs of the presence of active caspase-3 even in the absence of cell deathinducing agent (13).…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…2), and these proteases may have the potential to cause apoptosis by proteolytic activation of proapoptotic compounds present in the cytosol. Indeed, MCs were shown to be highly sensitive to apoptosis induced by secretory granule destabilization, and moreover, serglycin 2/2 MCs and MCs that lack individual serglycin-dependent proteases were less sensitive than were WT cells (16). A striking finding was that serglycin 2/2 cells, when eventually undergoing cell death, die preferentially by necrosis rather than by apoptosis (16).…”
Section: Serglycin Regulates Apoptosismentioning
confidence: 84%